An Analysis of Several Aspects of Fuel Cell (International Journal of Innovative Research in Computer Science & Technology, 2020)
Approximately 450 million individuals  worldwide suffer from mental and behavioural problems.  During their lifespan, one out of every four people will  acquire one or more of these diseases. Neuropsychiatric  illnesses account for 13 percent of total Disability Adjusted  Life Years (DALYs) lost globally due to all diseases and  accidents, with that figure anticipated to climb to 15  percent by 2020. Psychiatric diseases account for five of  the top 10 causes of disability and death worldwide.  Mental disorders not only impose a huge psychological,  social, and economic burden on society, but they also  elevate the risk of physical ailments. Given the existing  constraints in the effectiveness of treatment options for  decreasing disability caused by mental and behavioural  disorders, prevention is the only long-term strategy for  minimizing the burden imposed by these diseases. The  relevance of risk and protective factors in the development  of mental disorders and poor mental health has been  explored by social, biological, and neurological sciences.  From prenatal life onwards, biological, psychological, as  well as societal risk and protective factors, as well as their  interactions, have been uncovered. Because many of these  variables are changeable, they may be used as targets for  preventive and promotion efforts. This article covers a  variety of mental health topics.
Keywords: Cell; Current; Fuel; Hydrogen